1994
DOI: 10.1007/bf00402220
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of adhesion receptors in both lesional and non-lesional psoriatic skin

Abstract: Adhesion receptors and their ligands play a vital role in the immune system. We studied the expression of different adhesion receptors, using single- and double-staining immunohistochemical techniques, in both lesional and non-lesional skin specimens from seven psoriasis patients and in skin biopsy specimens from eight normal healthy controls. Our results showed an overall increased expression of several adhesion receptors in both lesional and non-lesional psoriatic skin. We consistently found an increased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 45 publications
2
40
1
Order By: Relevance
“…The overexpression of ICAM-1, VCAM-1 and E-selectin in psoriatic lesions is well documented [27]. In our study, the significant reductions in the expression of these markers and the pathological scores were observed after treatment, corroborating the results of the early studies.…”
Section: Discussionsupporting
confidence: 81%
“…The overexpression of ICAM-1, VCAM-1 and E-selectin in psoriatic lesions is well documented [27]. In our study, the significant reductions in the expression of these markers and the pathological scores were observed after treatment, corroborating the results of the early studies.…”
Section: Discussionsupporting
confidence: 81%
“…The first step of recruitment of leukocytes to the skin is the attachment of circulating cells to vascular endothelial cells, which is mediated by cell adhesion molecules, such as ICAM-1, VCAM-1, and Eselectin (21). It has been shown that the expression of these cell adhesion molecules is increased on dermal vessels of psoriatic skin (22)(23)(24)(25). To test the effect of miR-31 on endothelial cell-activating capacity of keratinocytes, we measured the expressions of ICAM-1, VCAM-1, and E-selectin in primary HUVECs incubated with culture medium from miR-31 inhibitor-treated keratinocytes.…”
Section: Mir-31 Regulates the Production Of Inflammatory Mediators Inmentioning
confidence: 99%
“…21,22 In a meta-analysis comprising 78 studies, increased levels of sICAM-1 and sE-selectin were detected in the serum of psoriasis patients. 23 MMPs degrade extracellular matrix components and are regarded as key regulatory molecules in the pathogenesis of cardiovascular disease.…”
Section: T Cells and Langerhans Cells Of The Inflammatory Infiltratementioning
confidence: 99%